Aloe Vera Compress in Children With Diagnosis of Dengue Hemorrhagic Fever (DHF) - Ramdani, Vikri Haikal; Firmansyah, Andan; Suhanda, Suhanda (INDOGENIUS, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an acute viral infection caused by the dengue virus, genus flavivirus, and family flaviviridae, which can be transmitted through the bite of Aedes mosquitoes, especially Aedes aegypti and Aedes albopictus. Objective: This case study describes the results of Aloe vera compress intervention in Dengue Hemorrhagic Fever (DHF) patients. Method: The case study with a nursing care approach where this research was carried out by collecting data starting from assessment, formulating a diagnosis, planning, carrying out actions, and carrying out intensive evaluation. This case study uses a descriptive method with the main aim of exploring the problem, providing an overview of the case study by analyzing in more depth the nursing care for the diagnosis of Dengue Hemorrhagic Fever (DHF) with the diagnosis of hyperthermia using the application of aloe vera compresses to Dengue Hemorrhagic Fever (DHF) patients. Result: The subjective data obtained was that the patient's mother said that her child's body temperature decreased after being given the Aloe vera compress intervention. Meanwhile, the objective data obtained was body temperature, which was originally 38.7°c to 36.8°C. Conclusion: The intervention carried out is thought to be effective in reducing body temperature in pediatric patients with Dengue Hemorrhagic Fever (DHF). Theoretically, this research does not conflict with previous research, so it can be a reference in conducting further research. Meanwhile, clinically, the Aloe vera compress intervention carried out to reduce body temperature in pediatric patients with Dengue Hemorrhagic Fever (DHF) can be an alternative for reducing body temperature in pediatric patients with Dengue Hemorrhagic Fever (DHF).